Identification of Novel Loci Associated With Hip Shape: A Meta‐Analysis of Genomewide Association Studies. (26th November 2018) - Baird, Denis A; Evans, Daniel S; Kamanu, Frederick K; Gregory, Jennifer S; Saunders, Fiona R; Giuraniuc, Claudiu V; Barr, Rebecca J; Aspden, Richard M; Jenkins, Deborah; Kiel, Douglas P; Orwoll, Eric S; Cummings, Steven R; et al.
ABSTRACT: We aimed to report the first genomewide association study (GWAS) meta‐analysis of dual‐energy X‐ray absorptiometry (DXA)‐derived hip shape, which is thought to be related to the risk of both hip osteoarthritis and hip fracture. Ten hip shape modes (HSMs) were derived by statistical shape modeling using SHAPE software, from hip DXA scans in the Avon Longitudinal Study of Parents and Children (ALSPAC; adult females), TwinsUK (mixed sex), Framingham Osteoporosis Study (FOS; mixed), Osteoporotic Fractures in Men study (MrOS), and Study of Osteoporotic Fractures (SOF; females) (total N = 15, 934). Associations were adjusted for age, sex, and ancestry. Five genomewide significant ( p < 5 × 10 −9, adjusted for 10 independent outcomes) single‐nucleotide polymorphisms (SNPs) were associated with HSM1, and three SNPs with HSM2. One SNP, in high linkage disequilibrium with rs2158915 associated with HSM1, was associated with HSM5 at genomewide significance. In a look‐up of previous GWASs, three of the identified SNPs were associated with hip osteoarthritis, one with hip fracture, and five with height. Seven SNPs were within 200 kb of genes involved in endochondral bone formation, namely SOX9, PTHrP, RUNX1, NKX3‐2, FGFR4, DICER1, and HHIP . The SNP adjacent to DICER1 also showed osteoblast cis‐regulatory activity of GSC, in which mutations have previously been reported to cause hip dysplasia. For three of the lead SNPs, SNPs in high LD ( r 2 > 0.5) were identified, which intersected with open chromatin sites as detected by ATAC‐seq performed on embryonic mouse proximal femora. In conclusion, we identified eight SNPs independently associated with hip shape, most of which were associated with height and/or mapped close to endochondral bone formation genes, consistent with a contribution of processes involved in limb growth to hip shape and pathological sequelae. These findings raise the possibility that genetic studies of hip shape might help in understanding potential pathways involved in hip osteoarthritis and hip fracture. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.